P81 The Increasing Secondary Care Burden Of Bronchiectasis In England. (10th November 2014) - Navaratnam, V; Millett, E; Hurst, JR; Thomas, SL; Smeeth, L; Hubbard, RB; Brown, J; Quint, JK
Abstract : Background: A recent study suggested that the bronchiectasis is now a relatively common condition in the UK. 1 The healthcare burden of bronchiectasis on secondary care, in terms of hospital admissions is also unknown, yet is essential for allocation of healthcare resources and planning of service pathways. We used data from Hospital Episode Statistics (HES) to determine age standardised annual hospital admission rates in England. Methods: We obtained annual number of hospital admissions (finished consultant episodes), total number of bed days and mean age at time of admission where bronchiectasis was the primary reason for admission for all hospital trusts in England. The ONS mid-year England population for 2011 was used as the standard population. Age specific admission rates for bronchiectasis were calculated for each year and these rates were applied to the 2011 population in order to generate annual standardised estimated number of admissions. An estimate of the average length of stay was calculated by dividing the total number of bed days by the total number of admissions for each calendar period. Linear regression was used to test for changes over time in mean age at admission and average length of stay. Results: In 2004 the total number of admissions was 8611 (11, 147 after standardisation) and this increased progressively up to 2011 when the number was 15, 885 (see Figure 1 ). The overall annual increase was 9% (Rate Ratio [RR] 1.09, 95% Confidence Interval [CI] 1.08 to 1.10; p < 0.0001). During the study period, the mean age at admission increased from 62 years to 65 years and the average length of stay decreased from 6.5 days to 4.7 days (p = 0.001). 60% of admissions were in women and admissions were more common in individuals over 60 years. Conclusions: Data on hospital admissions from bronchiectasis suggest that the disease burden is increasing. The cost of inpatient care, combined with outpatient disease monitoring and prescription of antibiotics pose a large burden on healthcare services. Reference: Quint J, Millett E, Hurst J, et al . P172 Time Trends in incidence and prevalence of bronchiectasis in the UK. Thorax 2012; 67:A138